PSYCHOLOGICAL CHARACTERISTICS OF COGNITIVE FIELD DEVELOPMENT IN PRIMARY CLASS STUDENTS - Boronova H.A. (Galaxy International Interdisciplinary Research Journal, 2022)
This article is devoted to the topic of psychological peculiarities of the development of conative sphere in elementary school students. The text of the article covers issues such as elementary school age, preparation for elementary school, students’ cognitive abilities, developmental features of knowledge processes, leading activities, game activities, communication skills and group relations skills, attention and its manifestation, information acquisition at the elementary school age.